2017
DOI: 10.1681/asn.2016080855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tenapanor on Serum Phosphate in Patients Receiving Hemodialysis

Abstract: Hyperphosphatemia is common among patients with CKD stage 5D and is associated with morbidity and mortality. Current guidelines recommend lowering serum phosphate concentrations toward normal. Tenapanor is a minimally absorbed small molecule inhibitor of the sodium/hydrogen exchanger isoform 3 that functions in the gut to reduce sodium and phosphate absorption. This randomized, double-blind, placebocontrolled trial assessed the effects of tenapanor on serum phosphate concentration in patients with hyperphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(125 citation statements)
references
References 42 publications
(59 reference statements)
5
110
1
Order By: Relevance
“…In a rat model of CKD and vascular calcification, tenapanor significantly decreased ectopic calcification, serum creatinine, phosphorus and fibroblast growth factor‐23 levels, and heart mass . Collectively, these findings have led to clinical trials of tenapanor for the treatment of hyperphosphatemia in patients with CKD on dialysis, in which the pharmacodynamic effects of the drug have been found to translate into clinically meaningful reductions in serum phosphate versus placebo …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a rat model of CKD and vascular calcification, tenapanor significantly decreased ectopic calcification, serum creatinine, phosphorus and fibroblast growth factor‐23 levels, and heart mass . Collectively, these findings have led to clinical trials of tenapanor for the treatment of hyperphosphatemia in patients with CKD on dialysis, in which the pharmacodynamic effects of the drug have been found to translate into clinically meaningful reductions in serum phosphate versus placebo …”
Section: Discussionmentioning
confidence: 94%
“…Studies in animals and humans have shown that tenapanor acts locally in the gut to selectively reduce absorption of sodium and phosphate . These effects may be beneficial in the management of constipation‐related disorders and CKD; tenapanor is currently being evaluated for the treatment of patients with IBS‐C and hyperphosphatemia in patients with CKD on dialysis . This phase 1 study evaluated the influence of the timing of food intake in relation to tenapanor administration on the pharmacodynamic effects of the drug in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there may be interactions between NHE3 and phosphate absorption based on the observation that tenapanor, a gut NHE3 inhibitor also inhibits phosphate absorption [64]. Thus, the gut-kidney-pulmonary-RV interaction could possibly also involve deranged mineral metabolism.…”
Section: Cardiorenal Syndrome Phosphate Balance and Pulmonary Hypermentioning
confidence: 99%
“…In order to attenuate the severity of hyperphosphatemia, dietary phosphate restriction and oral phosphate binders are first-line treatments for CKD stage 5D patients [17][18][19]. More recently, tenapanor, a small-molecule inhibitor of sodium/hydrogen exchanger isoform 3, was found to reduce serum phosphate concentrations significantly in patients receiving hemodialysis [20]. All of these data suggest that hyperphosphatemia in CKD patients is a critical cardiovascular risk factor.…”
Section: Introductionmentioning
confidence: 99%